MEDIATION OF BRAND AWARENESS IN THE RELATIONSHIP BETWEEN SOCIAL MEDIA MARKETING AND (E-WOM) KOREAN COSMETICS - Tiffany michelle Jatmiko; Auditia Setiobudi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the effect of Social Media Marketing on Brand Awareness and Electronic Word-of-Mouth (eWOM) in Korean cosmetic products, as well as to examine the mediating role of Brand Awareness in this relationship. The study employs a quantitative approach with 130 respondents selected through purposive sampling. Data analysis was conducted using SEM-PLS with SmartPLS software. The results of the reliability and validity tests indicate that the research instruments meet the required criteria, with Cronbach’s Alpha values exceeding 0.70 and Average Variance Extracted (AVE) values above 0.50, indicating that the data are reliable and valid. Furthermore, the path coefficient analysis reveals that Social Media Marketing has a positive and significant effect on Brand Awareness (0.690; t = 7.859; p = 0.000) and eWOM (0.484; t = 3.749; p = 0.000), while Brand Awareness also has a positive and significant effect on eWOM (0.427; t = 3.498; p = 0.000). In addition, Brand Awareness is proven to significantly mediate the relationship between Social Media Marketing and eWOM (0.295; t = 3.109; p = 0.002). These findings indicate that effective social media strategies can enhance brand awareness, which in turn encourages consumers’ online promotional behavior. Keywords: Social Media Marketing, Brand Awareness, Electronic Word-of-Mouth